OPTIMALISASI KINERJA PERSEDIAAN SUKU CADANG UNTUK PELAKSANAAN MAINTENANCE REPAIR OVERHAUL (MRO) DENGAN PENERAPAN COMPUTERIZED MAINTENANCE MANAGEMENT SYSTEMS (CMMS) (Studi Kasus di PT. Indonesia Asahan Aluminium) - Sutrisno Sutrisno; Gunawan MP; Raymond PT (Telematika, 2014)
PT.Inalum is a manufacturing company engaged in the aluminum smelting industry. PT.Inalum pengendaliaan system requires an inventory of spare parts to conduct maintenance, repair and overhaul (MRO). CMMS (Computerized Maintenance Management System) is a computerized maintenance system running on a LAN (Local Area Network). CMMS is influenced by three variables, namely an integrated maintenance, inventory and procurement so as to create a good maintenance should be supported by the inventory control of spare parts used in maintenance. CMMS aims to make the work more efficient and effective, especially in matters relating to maintenance. That as a benchmark to measure the performance of CMMs for spare parts inventory control is a key performance indicator (KPI). This study aims to evaluate and compare key performance indicators before and after implementation of CMMS for the implementation of MRO activities. Another goal to be achieved is to determine the factors that affect the value of the inventory of spare parts. Based on the results of data processing and analysis can be seen that by looking at a comparison of before and after implementation of CMMS on key performance indicators, it appears that there is an improvement in every parameter, one of which is the value of the inventory prior to the implementation of CMMS for $ 34,790,000.00 compared to after the application of the inventory value fell to $ 19,632,000.00. Factors that affect the value of the inventory is the inventory of spare parts, maintenance, procurement, and human resources.